1988
DOI: 10.1007/bf02350875
|View full text |Cite
|
Sign up to set email alerts
|

The production of pheromone clouds by spraying in the melon fly,Dacus cucurbitae coquillett (Diptera: Tephritidae)

Abstract: Abstract-Pheromone clouds sprayed by melon fly males were visually detected by focusing a beam of light at them during dusk when the males were vibrating their wings. The clouds were sprayed to the front, rear and upper sides of the male. We found that special morphological structures are used for spraying the pheromone clouds. When a male melon fly engages in calling behavior, sex pheromone droplets are excreted from his anus. This excretion is wiped off with the tarsus of his hind leg, and then it is deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…Examination of the volatiles emitted by live B. carambolae males not only revealed that these endogenous compounds were released into the air unchanged, but also coincided with courtship and mating periods of B. carambolae, which is at dusk. The release of sex pheromone by males to attract conspecific females is common in many species of tephritids including the Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Féron, 1959), the Carribbean fruit fly, Anastrepha suspensa (Loew) (Nation, 1972), the apple maggot fly, Rhagoletis pomonella (Walsh) (Prokopy, 1975) and in several other Bactrocera species (Kuba and Sokei, 1988;Kuba, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of the volatiles emitted by live B. carambolae males not only revealed that these endogenous compounds were released into the air unchanged, but also coincided with courtship and mating periods of B. carambolae, which is at dusk. The release of sex pheromone by males to attract conspecific females is common in many species of tephritids including the Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Féron, 1959), the Carribbean fruit fly, Anastrepha suspensa (Loew) (Nation, 1972), the apple maggot fly, Rhagoletis pomonella (Walsh) (Prokopy, 1975) and in several other Bactrocera species (Kuba and Sokei, 1988;Kuba, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…means of pheromone dispersal in most Bactrocera spp. (Kuba and Sokei, 1988), followed by mounting attempts onto other males in close proximity. Subsequently, with a further decrease in light intensity (300-600 lx), the number of males engaging in wing fanning activity increased (ϳ80%) and a whitish smoke was visible within the glass chamber.…”
Section: Male Volatile Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nishida (1988a) and found DMP and CF in the rectal gland of B. dorsalis males 6 d and as long as 20 d, respectively, after ingesting ME, indicating the capability for long-term retention of these chemicals. Importantly, ME metabolites have been detected in male volatile emissions (the pheromone "smoke" produced by Bactrocera males, Ohinata et al, 1982;Kuba and Sokei, 1988), DMP in the spray of B. dorsalis (Nishida et al, 1988a) and B. papayae and CF in the spray of B. carambolae . In addition, females have been shown to be attracted to the ME derivatives presented either singly or in a blend (Tan and Nishida, 1996;Nishida et al, 1997;Hee and Tan, 1998;.…”
Section: Fate Of Ingested Luresmentioning
confidence: 99%
“…Males of the melon fly, Bactrocera cucurbitae (Coquillett), form leks on non-host plants at dusk (Iwahashi and Majima, 1986) and court females by emitting a sex pheromone by vibrating their wings (calling) (Kuba and Koyama, 1985;Kuba and Sokei, 1988). An attracted female approaches the male and copulates with the male (Kuba and Koyama, 1985).…”
Section: Introductionmentioning
confidence: 99%